Education for all: Caribbean perspectives and imperatives - Miller, Errol L. (Inter-American Development Bank, 1992)
This book highlights the proceedings of the World Conference on Education for All and the Caribbean Consultation held in Kingston, Jamaica in 1989. It also attempts to identify specific policies and programmes appropriate for the Caribbean, and to suggest ways in which the global imperatives of meeting basic learning needs may be interpreted and implemented in the Caribbean. It examines specific case studies in Barbados, Haiti, and Jamaica, as well as promising and innovative programmes throughout the region
Keywords: Basic education